379 Real world retrospective study of patients with epithelial ovarian cancer: an international comparison. (4th December 2020) - Cheeseman, Sue; Levick, Bethany; Nam, Eunji; Lim, Subin; Rouzier, Roman; Bonneau, Claire; Kubelac, Milan Paul; Achimas-Cadariu, Patriciu A; Classe, Jean Marc; Bocquet, Francois; Becker, Sven; Guergova-Kuras, Mariana; et al.
Abstract : Introduction/Background: Clinical trials in Epithelial Ovarian Cancer (EOC) frequently examine treatment at a particular phase of the patient's disease trajectory. Few major studies have examined the management of patients from diagnosis to death. This international network was developed to compare treatment sequencing and outcomes from six centres across Europe and South Korea. Methodology: This retrospective cohort study used longitudinal data collected from electronic medical records from 6 European and South Korean treatment centres. A standard protocol & common data model was developed to capture consistent data for patients diagnosed between January 2012 and December 2018, with a minimum of 12 months follow-up. Full treatment data was collected and categorized in programmes of care based on exemplar patient narratives. An extensive data harmonization process was implemented to ensure different country and site medical records were interpreted in a common manner. Overall survival (OS) and time to next treatment (TTNT) were estimated using Kaplan Meier methodology and outcomes stratified by categories of interest. Each site analysed their own EMR data and shared aggregated results for comparison. Results: Table 1 demonstrates patient characteristics from six sites. In total the overall study cohort includes 2889 patients. Median age for each centre ranged from 53 to 67 years. The majority of patients were FIGO stage III (range 31% to 66%) and high-grade serous morphology (52% to 69.9%) Additional data on treatment pathways and outcomes for each centre will be presented. Conclusion: Preliminary analysis from this network suggests a consistent profile of adults treated for EOC across most contributing treatment centres in Europe, but with some substantial differences compared to patients treated at centres in South Korea and Romania. The establishment of a common data model between sites across five different countries allows for detailed exploration of the factors influencing differences in patient management and treatment outcomes in ovarian cancer patients. Disclosures: Sue Cheeseman: I receive consultancy fees from IQVIA Bethany Levick: I am an employee of IQVIA Eunji Nam: I have no conflict of interest to disclose Dongkyu Kim: I have no conflict of interest to disclose Roman Rouzier: I have no conflict of interest to disclose Claire Bonneau: I have no conflict of interest to disclose Paul Kubelac: served on a speaker's bureau for Roche, Bristol-Myers Squibb, AstraZeneca, Novartis. Patriciu Achimas-Cadariu: I have no conflict of interest to disclose Jean-Marc Classe: I have no conflict of interest to disclose François Bocquet: I have no conflict of interest to disclose Sven Becker: I have no conflict of interest to disclose Mariana Guergova-Kuras: I am an employee of IQVIA Geoff Hall: I receive grant support and consultancy fees from IQVIA